Serviço de integração entre alunos de graduação e empresas para o estágio profissional - Bassi, Nilton Galli (2020)
This report presents the work done to seize an opportunity by a private university in the city of São Paulo to help students find professional internship within their expectations and companies to find students within the profile of their needs. In this sense, the project of a service focused on the integration of these needs was elaborated, with the intention of creating value for the students, companies and the university. Its implementation has already begun, with the definition and acquisition of essential resources. Project development phases are detailed, from initial understandings of demand, followed by diagnosis to evidence of opportunity, strategy design, expected outcomes, available resources, capabilities and processes, including the digital platform, the change intervention process and what has already been achieved. In the elaboration of the proposal, an innovation was adopted in relation to the competitors, with the conception of the integration of interests among the stakeholders, so that their needs are effectively met, with the permanent exchange of information between them. The complexity faced at work is due to the fact that there are processes, structures and human behavior, already consolidated in the internal environment, resistant to changes with the new service, despite the concrete gains to the university. Notwithstanding being in the initial phase of implementation, the project has already impacted with significant changes, promoting process changes, people movement and the acceptance by the Rectorate and the Maintainer's direction the professional internship can be a productive new business and enhance the university's image in the Market.